Investigating the Gap between Newspaper Journalists' Role Conceptions and Role Performance in Nine European, Asian, and Latin American Countries. (October 2020) - Mellado, Claudia; Mothes, Cornelia; Hallin, Daniel C.; Humanes, María Luisa; Lauber, Maria; Mick, Jacques; Silke, Henry; Sparks, Colin; Amado, Adriana; Davydov, Sergey; Olivera, Dasniel
Based on a standardized operationalization of the watchdog, civic, interventionist, loyal-facilitator, infotainment, and service roles, this study combines survey ( N = 643) and content analysis data ( N = 19, 908) to explain gaps between newspaper journalists' role conceptions and the performance of their press organizations in nine countries from Latin America, Western Europe, and Asia. Taking an institutional approach by focusing on institutional influences on the conception–performance gap at three levels (individual, organizational, societal), our results show that these gaps are largest for the two roles most connected with the public functions of journalism, the civic, and the watchdog roles. Multilevel analyses offer significant evidence on that, across all six analyzed roles, the size of the gaps differed more clearly between journalists and between media organizations, than among countries. Although influences on an individual level (i.e., perceived autonomy) have some explanatory power, influences on the organizational level and, more specifically, ownership and codified editorial policies are the factors that best explain conception–performance gaps. The implications of these findings are discussed in light of the public skepticism about the performance of journalism and the media.